Profil Upaya-Upaya Remediasi Miskonsepsi Sains: Sebuah Tinjauan Literatur Sistematis - Putu Nita Kusuma; I Nyoman Suardana (Postgraduate, University of Mataram, 2025)
This study aims to describe: the trend of research on improving misconception in science (Physics, Chemistry, Biology), the remediated science concepts, the efforts to remediate science misconceptions. The research method used is systematic literature review (SLR) of the literature from 2019 to present (May 2025) on the Scopus, ERIC, and Google Scholar databases. So far, there has been no comprehensive review of integrated science misconception improvement in Physics, Chemistry, and Biology. The results showed that the trend of science misconception improvement from 2019 to present (May 2025) was mostly conducted in 2023 and was dominated by misconceptions at the high school level. The most remediated misconceptions are on the concept of Physics. The most applied efforts to remediate science misconceptions based on groups of media, models, strategies, methods, and learning approaches respectively are interactive media, conceptual change models, cognitive conflict strategies, refutation text methods, and multiple representative approaches. These remediation efforts can be integrated with each other to design more effective remediation techniques. These findings provide valuable insights for educators and researchers in designing more effective interventions to address science misconceptions at various levels of education, especially high school, and emphasize the importance of integrating various improvement efforts.